Structural behaviors of steel fiber-reinforced concrete-filled geotextile tube stub columns under axial compression. (June 2022) - Li, Tingchun; Ran, Jinlin; Chen, Dianhao; Du, Yiteng; Zhu, Qingwen; Zhang, Hao; Li, Weiteng
Abstract: Geotextile materials are recently widely used for concrete casting formwork system; however, concrete is brittle whose inherent abrupt failure property needs to be improved. In this study, a novel composite stub column that consists of external geotextile tube and internal steel fiber reinforced concrete (SFRC) core is proposed. A total of 36 circular concrete stub columns are tested to analyze the effects of fiber volume fraction and cross-sectional diameter on structural behaviors of geotextile-tubed SFRC under axial compression. Based on the test results, geotextile-tubed SFRC stub columns showed superior properties in terms of strength characteristic, strain capacity, modulus of elasticity, ductility and toughness, while the effect of cross-sectional diameter on structural behaviors of the stub columns became less obvious with increasing fiber volume fraction. Furthermore, the experimental data of SFRC stub columns was collected to evaluate the effect of formwork systems. It is evident that the geotextile tube can effectively solve problems of poor mixing and consolidation of SFRC with a high fiber volume fraction to ensure the concrete properties. Finally, a non-linear calculation model was also developed to evaluate the compressive behaviors for geotextile-tubed SFRC. Therefore, use of geotextile is recommended to applied as formwork system of SFRC members, which can provide researchers with more insights into the construction technique of concrete structures.